Keeping the Spark Alive: Being Motivated to Meet a Partner's Sexual Needs Sustains Sexual Desire in Long-Term Romantic Relationships. (May 2013) - Muise, Amy; Impett, Emily A.; Kogan, Aleksandr; Desmarais, Serge
How can couples keep the sexual spark alive in long-term relationships? The current study draws upon existing research and theory on both communal relationships and approach-avoidance models of social motivation to test the hypothesis that individual differences in the motivation to meet a partner's sexual needs, termed sexual communal strength, predict heightened feelings of sexual desire in long-term partnerships. In a 21-day daily experience study of 44 long-term couples, individuals higher in sexual communal strength engaged in daily sexual interactions for approach goals, and in turn, reported high levels of daily sexual desire. Sexual communal strength also buffered against declines in sexual desire over a 4-month period of time. These associations held after controlling for general communal strength, relationship satisfaction, sexual frequency, age, and whether or not the couples had children. These findings demonstrate the utility of extending theories of communal motivation to the sexual domain of relationships.